2017
DOI: 10.2147/idr.s144314
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and nephrotoxicity of colistin loading dose for treatment of extensively drug-resistant <em>Acinetobacter baumannii</em> in cancer patients

Abstract: BackgroundColistin is a last-line defense therapy against extensively drug-resistant Acinetobacter baumannii (XDR-AB). Despite a loading dose of colistin being applied in many clinical practices, studies evaluating the effect of the loading dose of colistin in cancer patients remain limited.Patients and methodsA retrospective cohort study of cancer patients who received either a loading or non-loading dose of colistin for treatment of XDR-AB was conducted. For each group, the clinical response, bacteriological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 16 publications
2
22
4
Order By: Relevance
“…Colistin-related nephrotoxicity rates have been reported as 6-55% in different studies [12]. The majority of these studies were performed using the RIFLE (Risk, Injury, Failure, Lost, End-stage kidney disease) or AKIN (Acute Kidney Injury Network) criteria for staging of AKI [13][14][15]. AKI was classified by using the KDIGO criteria in current studies [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Colistin-related nephrotoxicity rates have been reported as 6-55% in different studies [12]. The majority of these studies were performed using the RIFLE (Risk, Injury, Failure, Lost, End-stage kidney disease) or AKIN (Acute Kidney Injury Network) criteria for staging of AKI [13][14][15]. AKI was classified by using the KDIGO criteria in current studies [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Among the non-modifiable risk factors, higher age has been reported in many studies [14,17,19,22,28,29,30]. However, it is not known whether there is a linear effect of age on the risk of AKI or whether the risk may increase over a given age.…”
Section: Risk Factors For Nephrotoxicitymentioning
confidence: 99%
“…The most important variable associated with the development of nephrotoxicity is polymyxin dose [14,20,24,35,36,37,38,39,46,47]. Although evaluated in a few studies, the administration of loading doses has been found to increase the risk of nephrotoxicity in some studies [28,48], but not others [18,23,38,49]. Additionally, and possibly related to total drug exposure, a longer duration of treatment has been identified by some authors [21,29].…”
Section: Risk Factors For Nephrotoxicitymentioning
confidence: 99%
“…Most of the previous studies [8][9][10][11] showed that extendedspectrum β-lactamase-producing Enterobacteriaceae (ESBL-PE), multidrug-resistant (MDR) Pseudomonas aeruginosa, carbapenemresistant Enterobacteriaceae (CRE), Acinetobacter baumannii and methicillin-resistant Staphylococcus aureus (MRSA) have been increasingly identified as the predominant causative infection pathogens in cancer patients due to the phenomenon of antibiotics misuse [7,12]. However, antibiotics management for these infections is often limited.…”
Section: Introductionmentioning
confidence: 99%